Application of the Personal and Social Responsibility Teaching Model to Emotional Control and Responsibility - Muhamad Rafli Sahrullah; Tite Juliantine; Burhan Hambali (Universitas Negeri Semarang, 2026)
This study is motivated by the declining trend of students’ character values, particularly in the aspects of emotional control and responsibility within the school environment. Physical Education, Sports, and Health (PE) learning has a strategic role in developing these aspects through structured and value-based physical activities. This study aims to analyze the effect of the Teaching Personal and Social Responsibility (TPSR) learning model on students’ emotional control and responsibility. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The subjects of this study were eighth-grade students of Bandung State Junior High School 26 through cluster random sampling, with one class as the experimental group and one class as the control group. The research instruments used were the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) and the Personal and Social Responsibility Questionnaire (PSRQ). Data analysis was conducted using normality tests, homogeneity tests, independent samples t-test, and N-Gain analysis to determine the level of improvement effectiveness. The results showed that there was a significant effect of the TPSR model on students’ emotional control and responsibility (p < 0.05). The improvement in emotional control in the experimental group was categorized as moderately effective, while the improvement in responsibility was in the moderate category and more dominant compared to the control group. These findings indicate that TPSR is more optimal in developing responsibility aspects than emotional control. Therefore, it can be concluded that the TPSR model is effective for use in PE learning as an effort to strengthen students’ character, although its implementation needs to be carried out consistently and sustainably to achieve more optimal results.